2014
DOI: 10.1242/jeb.112425
|View full text |Cite
|
Sign up to set email alerts
|

Cockroach optomotor responses below single photon level

Abstract: Reliable vision in dim light depends on the efficient capture of photons. Moreover, visually guided behaviour requires reliable signals from the photoreceptors to generate appropriate motor reactions. Here, we show that at behavioural low-light threshold, cockroach photoreceptors respond to moving gratings with single-photon absorption events known as 'quantum bumps' at or below the rate of 0.1 s −1 . By performing behavioural experiments and intracellular recordings from photoreceptors under identical stimulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 35 publications
4
52
0
Order By: Relevance
“…; Honkanen et al. ), suggest that the visual capabilities of nocturnal insects are greater than we thought.…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations
“…; Honkanen et al. ), suggest that the visual capabilities of nocturnal insects are greater than we thought.…”
Section: Introductionmentioning
confidence: 53%
“…Nevertheless, recent research has shown that a variety of different body colors, including silver, yellow, and white, from a variety of nocturnal spiders can lure nocturnal insects (Chuang et al 2007(Chuang et al , 2008Blamires et al 2012Blamires et al , 2014Peng et al 2013;Zhang et al 2015). These results, and recent experiments showing the receptors of nocturnal insects responding to single photon sources (Kelber et al 2002;Honkanen et al 2014), suggest that the visual capabilities of nocturnal insects are greater than we thought.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…This represents a rather special case, because the animal relies more on tactile and olfactory cues in behavior while having large eyes and sensitive vision in the dark (Honkanen et al 2014;Mote 1990;Riemay 1984). …”
Section: Properties Of Kv Currents In Photoreceptorsmentioning
confidence: 99%